Towards sustainable economic growth: Threshold effects of bank-based financial development and recommendations for Vietnam - Ho, Linh Luong (TALENTA PUBLISHER UNIVERSITAS SUMATERA UTARA, 2025)
This paper investigates the relationship between bank-based financial development and economic growth in 14 Asia-Pacific economies over the period 2010-2021. Using a panel data framework with Pooled OLS and System GMM estimators to address potential endogeneity, the results reveal nonlinear patterns: certain measures of financial development exhibit an inverted U-shaped relationship with growth, while another measure shows a U-shaped relationship. These findings suggest that both insufficient and excessive financial development can be detrimental, and that the growth-enhancing effects may emerge only beyond specific thresholds. Policy recommendations for Vietnam emphasize strict supervision of credit institutions, encouraging commercial banks to adopt digital transformation, inflation stability, stock market deepening, and targeted attraction of high-quality foreign direct investment.